IOT-BASED WATER LEVEL MONITORING SYSTEM OF SITU RAWA BESAR - Wati, Erna Kusuma; Santoso, Hari Hadi; Laksono, Aryo (MSJ : Majority Science Journal, 2024)
Pancoran Mas, Depok city has a water catchment area, namely Situ Rawa Besar. Situ Rawa Besar has the potential to overflow during the rainy season which caused flooding in 2020. The water level of Situ Rawa Besar is not monitored in real time so that information on the increase in water level is late to reach the community. Thus, an IoT-based water level monitoring system using ultrasonic sensors was made so that the community was able to monitor the state of Situ Rawa Besar in real time through a prepared website. In order to use the ultrasonic sensor module, there was a failure to read the water level in previous studies. So in addition to monitoring the water level in Situ Rawa Besar, the purpose of making this system is to prove that ultrasonic sensors can be used in water environments such as situ. System testing was carried out at Situ Rawa Besar and at the Prototype. This system is able to monitor the water level for 24 hours with electrical power provided from batteries integrated with solar panels. Testing was carried out on 6 days with an average water level of 70-72cm (alert level). All height data for 6 days is uploaded to the Thingspeak website and can be seen by anyone. Based on the research on the prototype, the system is able to measure the height from 0-182 cm and turn on the alarm when the height is more than equal to 100 cm.